Reviewing the impact of studying in a Business School: Insights on students' Sustainability perception and sustainable behaviour triggering - Almeida, I. D. de (Proceedings of 29th EurOMA Conference. Brilliance in resilience: Operations and supply chain management’s role in achieving a sustainable future, 2022)
Sustainable actions and attitudes are part of the Sustainable Development Goals. This exploratory study is based on an assessment of sustainability in higher education institutions and a literature review. A qualitative research approach is applied, using a questionnaire adapted from the European University Association (EUA) to explore the perceptions and opinions of different academic communities on some collective greening measures. The qualitative data analysis will be based on the survey conducted on a non-probabilistically selected sample of campus users. This research aims to find out the challenges and initiatives practised in defence of sustainability and to contribute to a change in awareness in the campus community.